The Influence Of Work Life Balance And Flexible Work Arrangements On Employee Performance At Pt. Mahkota Group, Tbk - Hulu, Fatolosa; Baene, Eduar (MSJ : Majority Science Journal, 2024)
This research aims to explore the positive and significant implications of the relationship between work-life balance and flexible work arrangements on employee performance at PT Mahkota Group, TB, a business entity that exists in an ever-changing and fast-paced context. In an ever-evolving world of work, a deep understanding of how work-life balance and flexible work arrangements affect employee performance is crucial for organizational survival and success. Using a quantitative approach and linear regression analysis techniques, this study found strong evidence of a positive and significant relationship between these two variables and employee performance. This research provides a solid foundation for company management to implement policies that are more adaptive and inclusive of employee needs, and strengthen their commitment to improving employee welfare. This research not only contributes to the academic understanding of the dynamics of the relationship between work-life balance, flexible work arrangements, and employee performance, but also provides practical direction for company management in achieving competitive advantage through the implementation of human resource management strategies that focus on work-life balance and optimal performance.